Early endoscopic finding of esophageal thermal injury after having spicy hot pot. Issue 3 (2nd March 2015) - Wu, Chia‐Hsien; Bair, Ming‐Jong; Lin, I‐Tsung; Lee, Yuan‐Kai; Chen, Huan‐Lin
Summary: We herein present the case of a woman who had esophageal thermal injury after having a spicy hot pot. The patient came to us with complaints of odynophagia, dysphagia, and burning sensation at the throat and upper chest while eating or drinking for 1 day. An upper endoscopy was conducted 1 day after the onset of symptoms, which showed a linear, disrupted bullae‐like lesion with a thin detached membrane. Our report depicts the early endoscopic finding of esophageal thermal injury following the ingestion of hot food. The finding is different from what has been often reported as the "candy‐cane" appearance of esophageal injury, which results from the ingestion of hot liquid.